Pendampingan Zakat Produktif Berbasis Masyarakat Desa Sukoharjo Kepanjen Kabupaten Malang - Ika Anggraini; Sri Muljaningsih; Dwi Retno Widiyanti; Wisam Zuhdi; Surya Nusantara; Bilal Mu’taz Zuhair (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Based on data from the Central Statistics Agency (BPS) in March 2021, Indonesia's Gini ratio was at 0.381, or an increase of 0.001 points compared to the Gini ratio in September 2019 of 0.380. Indonesia's inequality rate reaches 49 percent. The following is the 2018 Global Wealth Report from the Boston Consulting Group which notes that the richest 10 percent of Indonesia's people control 75.3 percent of the wealth of the Indonesian population. In the Islamic perspective, zakat is one of the useful philanthropic instruments as a solution to this inequality. With the majority of the population (86.88%) being Muslim, Indonesia has a potential for zakat realization of 326.7 trillion. However, so far the realization of the potential for zakat is only 5 percent (BAZNAS, 2021). Therefore, zakat is present as a solution to reduce economic inequality in the Islamic perspective along with optimizing the utilization of zakat through community-based productive zakat assistance activities. This journal seeks to describe the form of community service socialization activities in Sukoharjo Village, Kepanjen Malang Regency, as a form of implementing the Tri Dharma of Higher Education. The socialization of productive zakat assistance is very important not only as a solution to the problem of inequality, but also opens a new paradigm regarding the utilization of zakat from various perspectives, both social, cultural, agricultural, animal husbandry, interdisciplinary science and other economic fields.